2018
DOI: 10.13189/ujer.2018.061102
|View full text |Cite
|
Sign up to set email alerts
|

STEM Education Research: Content Analysis

Abstract: People need to be qualified to adapt to innovations caused by the rapid change in information and technology. This would be realized with the integration of technology into education. In order to subsist in the world of science and technology the disciplines with an important role both now and in the future are science, technology, engineering and mathematics. In this regard, the number of studies conducted on the improvement of science, technology, engineering and mathematics (STEM) education is also increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
1
20
0
2
Order By: Relevance
“…Qualitative method was used in some of the analyzed doctoral theses and quantitative method was used in a few. Similarly, Çevik (2017) and Kaleci & Korkmaz (2018) found that the studies based on qualitative method were the most common in the studies investigated in their study. It is concluded that action research (Hacıoğlu, 2017) and design-based research methodology (Gül, 2019) are frequently preferred in the doctoral theses analyzed.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Qualitative method was used in some of the analyzed doctoral theses and quantitative method was used in a few. Similarly, Çevik (2017) and Kaleci & Korkmaz (2018) found that the studies based on qualitative method were the most common in the studies investigated in their study. It is concluded that action research (Hacıoğlu, 2017) and design-based research methodology (Gül, 2019) are frequently preferred in the doctoral theses analyzed.…”
Section: Discussionmentioning
confidence: 81%
“…In this context, the fact that it has been studied with all the relevant groups and the most secondary school students shows that STEM education is being worked with a group that is expected to contribute, and this situation can be evaluated as contributing to the field. In the studies examined in the literature review conducted by Kaleci & Korkmaz (2018), it was determined that the most research was carried out with primary school students. In the theses analyzed has been determined that the highest number of studies in the theses on STEM were conducted with 31-50 people (Hiğde, 2018;Koçyiğit, 2019), then 71-100 people, then 51-70 people (Ata Aktürk, 2019) and 11-30 people (Tunç, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly crucial given that integration of STEM education has increasingly been growing in both developed and developing countries (El-Deghaidy & Mansour, 2015). Kaleci and Korkmaz (2018) have identified STEM education"s contributions to society which include the development of scientific and technological skills, contribution to sustainable growth, and the improvement of STEM literacy while drawing its connection to the society, school, and work, among others. Given this role played by STEM education in the global community, one cannot deny the need to pay attention to it.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of art elements in education can improve student inquiry skills, problemsolving skills, and creative thinking (Psycharis, 2018), make learning more exciting, increase the creativity of students and develop knowledge and social abilities (H. Kim & Chae, 2016). Besides, the application of STEM learning can increase the level of student productivity (Kaleci & Korkmaz, 2018). So there was a shift from STEM to STEAM (Psycharis, 2018).…”
Section: Introductionmentioning
confidence: 99%